The School Management in The Islamic-Based Excellent Vocational High School - Iswadi, Iswadi; Iriansyah, Herinto Sidik (Universitas Malikussaleh, 2020)
Management plays an important role in building the quality of an institution. especially schools, consequently, quality management is needed to achieve these goals. The reality in the field shows that management is a discourse that has not yet received serious attention. Therefore, this study aims to gain a deep perception of the Management of Schools in Islamic Vocational High Schools. This study employs a qualitative approach with a case study method. The results of this study are classified into several steps. First, planning, Second, organizing, Third, mobilizing, Fourth, supervision. The results of the study indicate that in common the management of schools in Panglima Besar (PB) Soedirman Islamic Vocational School Jakarta takes place following the management functions applied in schools, this can be observed from the curriculum planning process carried out comprehensively and based on Islamic principles. Organizing activities in student affairs by linking all study programs and cross committees, the good student progress, and comprehensive supervision covering all supporting elements as well as supervision involving various stakeholders using the religious-based management approach. The harmonious coordination of the scholarly community-based academic scheme in the four fields of expertise makes Panglima Besar Soedirman Islamic Vocational School Jakarta one of the references to a superior Islamic-based vocational school in the Jakarta community.